Empirical study on the factors influencing the successful aging of the middle-aged and older adult community volunteers - Chen, Chien-Chih; Lan, Yu-Li; Yan, Yu-Hua (Frontiers in Public Health, 2023)
Background The pursuit of successful aging is currently the most important research and policy issue in an aging society. Participating in voluntary services can help middle-aged and older adults recognize the positive value and benefits of social participation, feel a sense of happiness and accomplishment, and improve their overall life satisfaction, which can also contribute to successful aging. This study wants to understand whether the participation motivation and expectation confirmation of middle-aged and older adult volunteering will affect their continuous participation behavior and successful aging because of the satisfaction of actual participation? Objective This study explores the factors related to middle-aged and older adult volunteering participation and their impact on successful aging. Methods Middle-aged and older adult volunteering from the East Taiwan Community Development Association and community care centers were taken as the research objects. Convenience sampling was used to select volunteers who were over 45 years old (inclusive) and have participated in voluntary services over five (inclusive) times in the last 6 months. Respondents completed the questionnaire through self-completion or face-to-face interviews with the interviewer. The measurement tools include engagement motivation, expectation validation, satisfaction, ongoing engagement, and successful aging. Results A total of 536 questionnaires were distributed of which 498 were valid and 38 invalid. The questionnaire recovery rate was 92.91%. Statistical findings include: (1) Those who perceived that their health was good had a better successful aging status than those who perceived that their health was normal. (2) The volunteering participation motivation and expectation confirmation of middle-aged and older adults significantly affected their volunteer participation satisfaction. (3) Participation motivation and expectation confirmation predicted 50.8% of satisfaction. (4) Satisfaction predicted 47.1% of continuous participation. (5) Continuous participation and satisfaction had a predictive power of 65.1% for successful aging. Conclusion This study confirms that the motivation and expectation of middle-aged and older adult to participate in volunteering will affect their continuous participation behavior and successful aging status through satisfaction. The research results can be used as a reference for the practical work plan of volunteering.